WOMEN’S FREEDOM FROM PATRIARCHY IN ABI DARE’S ‘THE GIRL WITH THE LOUDING VOICE’ (International Conference on Social and Islamic Studies, 2022)
This research discusses women’s freedom from patriarchy in Abi Dare’s The Girl with the Louding Voice. The aim of this research is to analyze how women get their freedom from patriarchy by becoming the independent women. The object of this research is a novel by Abi Dare entitled The Girl with the Louding Voice (2020). This research uses a qualitative descriptive method and theory Independent women of Simone de Beauvoir  which can be divided into three: Independent women and work, independent women and freedom, independent adventure.The researchers collect the data by reading, understanding, searching, and marking the data and then the researchers identified, qualified, and analyzed the data. The result shows that women against patriarchy such as subordination, exploitation, oppression and achieve their freedom by becoming independent women was found in the novel.